Identification of regulatory motif for enhancing expression of oil palm fatty acid biosynthetic genes - Abu Hanifiah, Farah Hanan; Abdullah, Siti Nor Akmar (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
Stearoyl-ACP desaturase (SAD) plays a central role in regulating the levels of unsaturated fatty acids in plant storage lipid and is a potential candidate gene for improvement of oil traits in oil palm. This study aims to discover a new regulatory motif that can enhance or suppress the activity of the oil palm SAD1 promoter. The SAD1 promoter of 1111 bp in size was isolated and its 5’ deletion fragments of 698bp (D1), 643bp (D2), 594bp (D3), 516bp (D4), 444bp (D5) and 413bp (D6) were generated and cloned into a pBGWFS7.0 vector harbouring both the β-glucuronidase (GUS) and green fluorescent protein (GFP) reporter genes. The recombinant plasmids were bombarded into oil palm mesocarp tissues at the start of oil synthesisand transient expression assay of both reporter genes were performed. GUS activity in the D3 deletion construct (-486 to +108) was significantly increase while the D2 (-535 to +108) deletion construct directed the lowest expression of GUS reporter gene. In order to determine the presence of a negative cis-acting regulatory element(s) whose removal led to the increase GUS expression in the deleted -535 to -486 (49bp), an electrophoretic mobility shift assay (EMSA) was carried out. The 49bp region interacted with the nuclear protein extract from mesocarp but not to the extract from leaves. Fine-tuned analysis of this 49 bp region using truncated DNA and nucleotide mutations led to the identification of a novel GCTTCA motif. The presence of LECPLEACS2 (TAAAAT) is essential for effective competition by GCTTCA in binding to mesocarp nuclear protein extract. GCTTCA with one variant nucleotide is also found in the promoter sequence of acyl-carrier protein (ACP3), an important co-factor for plant fatty acid biosynthesis supporting the important role of this new found motif in regulating gene expression in the mesocarp tissues.